Benchmarking Banking Sector Efficiency Across Regional Blocks in Sub-Saharan Africa : What Room for Policy? - Boutin-Dufresne, Francois (IMF Working Papers; Working Paper ;, 2013)
This paper examines the determinants of net interest margins in four regional blocks in Sub-Saharan Africa and one comparator block in the Eastern Caribbean. Using bank-level data, we find that countries with a high level of operating costs, a high ratio of equity to total assets and high treasury bill interest rates have higher net interest margins. Moreover, high operating costs are associated with low measures of institutional quality and a small size of bank operations. We find support for the view that market structure is also partly responsible for high net interest margins in Sub-Saharan Africa. If interpreted causally, high operating costs and a high ratio of equity to total assets and, indirectly, institutional factors such as the rule of law, are the most important factors in accounting for high interest margins in the East African Community, relative to other regions.